Cobre em solos cultivados com hortaliças no Rio Grande do Sul e efeitos de concentrações em plantas de beterraba e repolho - Schmitt, Odair José (2018)
The objective of this work was to make a diagnosis of copper content in soils nowadays used for horticultural crops in different regions of Rio Grande do Sul state, to infer about its potential environmental contamination, its potential toxicity on morphological, physiological, biochemical and growth parameters of beet and cabbage plants, and health risks associated with the consumption of these vegetables. Soils were sampled for determinations of soluble, available and total Cu levels in protected cultivation (CP), open field (CA) and non-anthropogenic (CN) areas (Study1). To determine Cu accumulation in different tissues of beet and cabbage plants and its potential toxicity , two experiments were carried out using a soiless experimental set-up with nutrient solutions containing Cu concentrations of 0,02; 0.27; 0.52; 0.77 and 1.02 mg Cu L-1 (Study 2) and 0.00; 0.52; 1.02; 1.52; 2.02 and 2.52 mg Cu L-1 (Study 3). The Cu contents in soil solution, available and total fractions in areas of CA and CP were higher than in CN. The Cu contents in shoot tissues of both species and in beet taproots increased with Cu concentrations in the nutrient solution, reaching phytotoxic levels. Health risks might face from in natura consumption of beet taproots and cabbage.